The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10973-017-6391-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and flammability of polyurethane foams chemically reinforced with POSS

Abstract: This work reports on the thermal stability and flammability of a novel class of rigid polyurethane foams chemically modified by functionalized 1,2-propanediolisobutyl POSS (PHI-POSS) as a pendant group and octa (3-hydroxy-3-methylbutyldimethylsiloxy) POSS (OCTA-POSS) as a chemical cross-link. The foamed hybrid materials were prepared in a three-step process using a sorbitol-based polyether polyol, polymeric 4,4 0 -diphenylmethane diisocyanate and dimethyl propane phosphonate as a flame retardant. The addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…In order to increase above-mentioned parameters of polyurethanes, different strategies can be applied. Thermal stability and flame retardancy of PU composites can be improved by incorporation of specific comonomers into the polymer backbone or by blending with fillers of different nature (silsesquioxanes, borax, graphite, carbon fillers, silicates, metals, graphene, phosphates, and many others) [42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase above-mentioned parameters of polyurethanes, different strategies can be applied. Thermal stability and flame retardancy of PU composites can be improved by incorporation of specific comonomers into the polymer backbone or by blending with fillers of different nature (silsesquioxanes, borax, graphite, carbon fillers, silicates, metals, graphene, phosphates, and many others) [42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…For SEM analysis, samples were mounted on aluminium studs using adhesive graphite tape and sputter‐coated with gold before analysis. The pore structure properties, such as average cell size, average cross‐section of cells and anisotropy index of cells, were determined using Image‐Pro Plus software …”
Section: Methodsmentioning
confidence: 99%
“…The pore structure properties, such as average cell size, average cross-section of cells and anisotropy index of cells, were determined using Image-Pro Plus software. 26,28 TGA was carried out using a TA Instruments 500. Temperature programs were run from 30 to 800 ∘ C at a heating rate of 10 ∘ C min −1 under a nitrogen atmosphere.…”
Section: Characterizationmentioning
confidence: 99%
“…Therefore, studies on the effects of using various additives on the thermostability of PU foam have become popular in recent years. Michałowski et al . applied polyhedral oligomer silsesquioxane (POSS) modifier to improve the thermostability and flammability of rigid polyurethane foams, and they found that the cellular structure of the foam was dependent on the addition of POSS modifier.…”
Section: Introductionmentioning
confidence: 99%
“…8 Therefore, studies on the effects of using various additives on the thermostability of PU foam have become popular in recent years. Michałowski et al 9 applied polyhedral oligomer silsesquioxane (POSS) modifier to improve the thermostability and flammability of rigid polyurethane foams, and they found that the cellular structure of the foam was dependent on the addition of POSS modifier. Zheng et al 10 used a one-step method to make PU foams using microwave liquefied sugar beet pulp (LSBP) and polymethylene polyphenyl isocyanate, examining the influence of the NCO─/OH─ ratio on the mechanical, thermal, and microstructural properties of LSBP/PU foam.…”
Section: Introductionmentioning
confidence: 99%